Portable biosensors and point-of-care systems - Kintzios, Spyridon E. (Healthcare technologies series, 2017)
This book describes the principles, design and applications of a new generation of analytical and diagnostic biomedical devices, characterized by their very small size, ease of use, multi-analytical capabilities and speed to provide handheld and mobile point-of-care (POC) diagnostics.